56 Ageism in Myelodysplastic Syndrome. (16th March 2021) - Hogan, P; Enright, H; Ryan, D; O'Neill, D
Abstract: Background: Myelodysplastic Syndromes (MDS) are a group of haematological disorders which are common in older people and can be amenable to treatment. Ageism has previously been identified in studies of treatment for conditions affecting older people. Objectives: To assess for the presence of ageism in studies of treatment for MDS. Design: A review of the Cochrane Library of Systematic Reviews. Setting: Desk-based. Methods: Systematic reviews were analysed to determine: use of age as an exclusion criteria in randomized-control trials (RCTs); the comparison of ages of patients in RCTs to that of the median age of patients with MDS; exclusion of patients from RCTs on the basis of dementia or other conditions associated with ageing. Results: 17 reviews were identified, 2 of which were suitable for analysis. The two remaining systematic reviews reported data on 13 RCTs—of which 2 did not report age. The median age of all patients was 68. Three RCTs used a maximum age limit for therapy—one of which was lower than the median age of diagnosis of MDS. More recent studies tended to include older patients. No studies excluded patients on the basis of cognitive status. Conclusion: There was some evidence of ageism identified in studies of treatment for MDS. There was limited data available in the Cochrane database of Systematic Reviews, which may itself be suggestive of ageism in such reviews.